A study on growth formation of nano-sized magnetite Fe3O4 via co-precipitation method - Lim, Y.S.; Lai, C.W.; Hamid, Sharifah Bee Abd; Julkapli, N.M.; Yehya, W.A.; Karim, M.Z.; Tai, M.F.; Lau, K.S. (Taylor & Francis, 2014)
A simple and cost-effective chemical co-precipitation of aqueous ferrous and ferric salts was used to synthesis controlled size of magnetite iron oxide nanoparticles. The titration reactions between the aqueous Fe2+/Fe3+ salt solutions were controlled by an autotitrator unit with continuous addition of 1 M sodium hydroxide under different heating temperatures from 30 up to 80 degrees C in oxidising atmosphere. Then, further investigation on the degree of crystallinity of magnetite iron oxide nanoparticles was conducted by altering the concentration of Fe2+/Fe3+ ions in the ratio of 1:1, 1:1.25, 1:1.5 and 1:2. The resultant magnetite iron oxide nanoparticles were characterised by using X-ray diffraction, field emission scanning electron microscopy and Fourier transform infrared spectroscopy. The ratio of Fe2+/Fe3+ salt solutions and heating temperatures played a crucial role in controlling the morphology, crystallinity and particle sizes of magnetite magnetite iron oxide.